Utilization of Casgot and Eco Enzyme Fertilizer as Nutrient Support to Increase the Growth of White Cooperate (Brassica Pekinensis L) of the Tahono Variety in Karo District - Zulfansyah, Ichpan; Yulianita, Siska; Balatif, Fuad; Panjaitan, Faisal Azhari Baldan (PT Inovasi Pratama Internasional, 2024)
Efforts to increase the growth of white mustard plants can be done by providing Kasgot Fertilizer and POC Eco enzyme treatment. If you look at the correct dose, type, time and method of fertilization, the plant's response to fertilization will increase growth and yield. This research was carried out with the aim of determining the effect of plants on the concentration of Kasgot and POC Eco enzyme in white mustard plants. This research was repeated three times using a two-way randomized block design (RAK). The cassava concentration factor (K) has 4 levels, K0 (control), K1 (2 kg/plot), K2 (3 kg/plot), K3 (4 kg/plot). POC Eco enzyme factor (C) consists of 3 levels, namely E0 (control), E1 (20 ml/L), E2 (35 ml/L). Observation parameters include plant height, stem diameter, leaf width for each sample plant. Application of Kasgot Fertilizer had a significant effect on plant height and stem diameter of white mustard plants (3 kg/plot). The administration of POC Eco enzyme had no significant effect on all parameters observed. The interaction of providing Kasgot Fertilizer and POC Eco enzyme had no significant effect on all the treatments observed.